(3KeQI cdGe CQSWhWGdjS hZjQg aj GdfHGJs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3deG hLOJ Cf cJGH CQSWhWGdjS ai GdfHGJ eabhQkG hdG bOQI dHTQ Ydi EYGOI JUfja jabO ef JUGfja gPG GdQLd LeYJ SGFQ eG hLOJg ai gPG Gdaf ef ebGdg ef CbGhjd s
(3BNQgG (B:s
(3hGdhQb GdPi jchf dCLd GdKeQI jHbi eY GdKeQI heG cGf daX GdZU CjVkG jHbi OGFekG , Je cJGH GdfHGJ hddg GdMeO hGdTcQ OGFekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/2) s
Keywords: (3GdadSaI hGdefWbs